2012
DOI: 10.1007/s00128-012-0669-9
|View full text |Cite
|
Sign up to set email alerts
|

Air Quality Status During Diwali Festival of India: A Case Study

Abstract: The PM(2.5) and PM(10) samples were collected during Diwali celebration from study area and characterized for ionic concentration of four anions (NO(3) (-), NO(2) (-), Cl(-), SO(4) (2-)) and five cations (K(+), Mg(2+), NH(4) (+), Ca(2+), Na(+)). The results showed that the ionic concentrations were three times compared to those on pre and post Diwali days. Predominant ions for PM(2.5) were K(+) 33.7 μg/m(3), Mg(+) 31.6 μg/m(3), SO(4) (2-) 22.1 μg/m(3), NH(4) (+) 17.5 μg/m(3) and NO(3) (-) 18 μg/m(3) and for PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Firecrackers contain large amount of nitrates and sulphates of lead, cadmium, potassium, ammonium and magnesium (Rao et al, 2012). Wang et al (2007) had used K and Cl as the elements for fireworks indicators.…”
Section: Elements and Ionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Firecrackers contain large amount of nitrates and sulphates of lead, cadmium, potassium, ammonium and magnesium (Rao et al, 2012). Wang et al (2007) had used K and Cl as the elements for fireworks indicators.…”
Section: Elements and Ionsmentioning
confidence: 99%
“…This observation has been further stressed upon in the later section while appreciating enrichments. Rao et al (2012); 24-h average on Diwali day. 3 Perrino et al (2011); 24-h average on Diwali day.…”
Section: Diurnal Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that extreme air quality has adverse effects on citizens [11]- [13]. :00 PM 8:00 PM 9:00 PM 10:00 PM 11:00 PM 12:00 AM 1:00 AM 2:00 AM 3:00 AM 4:00 AM 5:00 AM 6:00 AM 7:00 AM :00 AM 7:00 AM 8:00 AM 9:00 AM 10:00 AM 11:00 AM 12:00 PM 1:00 PM 2:00 PM 3:00 PM 4:00 PM 5:00 PM 6:00 PM The increase concentration of particulate matter (PM 10 & PM 2.5 ) leads to increase in the cations concentration in atmosphere which causes serious health hazard [14]. Heavy metal characterization is shown in Figure 10 and Figure 11 for PM 10 and PM 2.5 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Among all detected water-soluble ions, K + was considered a reliable indicator of PM generated by FW burning (Drewnick et al, 2006;Wang et al, 2007;Shen et al, 2009;Chang et al, 2011;Feng et al, 2012;Rao et al, 2012;Tsai et al, 2012;Ambade and Ghosh, 2013;Chatterjee et al, 2013;Pachauri et al, 2013;Cheng et al, 2014;Lin et al, 2014;Tian et al, 2014;Yang et al, 2014). High concentrations of other ions, such as Mg 2+ , Ca 2+ , and Na + , are often detected during FW periods (Wang et al, 2007;Feng et al, 2012;Rao et al, 2012;Tsai et al, 2012,Chatterjee et al, 2013Ambade and Ghosh, 2013;Cheng et al, 2014;Crespo et al, 2014;Lin et al, 2014). Increased Cl − /Na + ratios and decreased Cl − /K + ratios of ambient fine particles were sometimes suggested to be indicators of FW burning (Tsai et al, 2012;Pachauri et al, 2013).…”
Section: Water-soluble Ionsmentioning
confidence: 99%